The Extent of Prevalence of Cognitive Malformations among Female Counselors in Qurytte City, KSA, and its Relation to Future Anxiety - Maryam Alanazi (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The current study aimed to identify the extent of cognitive distortions of female student counsellors in the Qurayyat Governorate and their future anxiety. To achieve the objectives of the study, the study was applied to a sample of (55) counselors. Two scales were developed: cognitive distortions, consisting of (46) items and five dimensions, and the future anxiety scale, consisting of (26) items and three dimensions. The results of the study revealed that there is a medium degree of cognitive distortions among the female counselors in general, and that there is a medium degree of anxiety among the counselors. Dimensions of cognitive distortions predict (25%) of future anxiety. The dimension of self-blame significantly predicts future anxiety. Female counselors generally do not differ in cognitive distortions according to social status. The study recommended the necessity of holding training workshops for the female counselors to reduce their cognitive distortions, especially in self-blame and reasoning.